Dampak Pengembangan Pariwisata Terhadap Kesejahteraan Sosial-Ekonomi Masyarakat Lokal: Studi Kasus di Destinasi Wisata Pantai Gelora, Kabupaten Sumbawa, NTB - Nirmala Selbia; Prayitno Basuki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Tourism as a national strategic sector continues to grow in Indonesia. One of the city that continues to develop its tourism is Sumbawa City. Tourism is an important sector developed by the government in the hope that it can have a positive impact on changing socio-economic conditions in a better direction. This study aims to know the influence of the Gelora beach tourist attraction to the socio-economic of Rhee Loka people. This research is a qualitative with qualitative descriptive approach. Techniques of collecting data uses interviews, observation, and documentation. Informant selection technique uses purposive sampling, with validity of data triangulation. The process of data analysis uses interactive analysis by Miles and Huberman, these are data collection, data reduction, data presentation, and drawing conclusions. The results of this study show that social change that is appeared in Rhee Loka society is a way of thinking of the society that begin to progress and developing. Changes are also established in the economic field, that is livelihoods and increasing income in Rhee Loka society. Positive impacts are easy to get clean water, new job opportunities, increased welfare, easy road access, advanced in people mindset. While the negative impact is the westernization are copying by local people, and the potential for crime.